A Sistem Informasi Kepegawaian Menggunakan Lean Software Development: (Studi Kasus: Universitas Catur Insan Cendekia) - Silviani, Yuki; Ridho Taufiq Subagio; Mohammad Umar Fakhrudin (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2025)
Personnel management at Universitas Catur Insan Cendekia is still conducted manually, making it prone to errors, data duplication, and limited accessibility. The career development submission process is also not yet computerized, resulting in low administrative efficiency. This study develops a Web-Based Personnel Information System using the Lean Software Development method with Laravel, HTML, CSS, PHP, and JavaScript. The system stores personnel data and documents, facilitates career development submissions, and provides centralized, accurate, and real-time access. The results are expected to improve efficiency, reduce errors, and support integrated monitoring for HR, study programs, faculties, and the rectorate in decision-making and enhancing the professionalism of academic and administrative staff.